Induced Intermediate Mesoderm Combined with Decellularized Kidney Scaffolds for Functional Engineering Kidney - Zhang, Jianye (Tissue Eng Regen Med, 2019)
BACKGROUND: Chronic kidney disease is a severe threat to human health with no ideal treatment strategy. Mature mammalian kidneys have a fixed number of nephrons, and regeneration is difficult once they are damaged. For this reason, developing an efficient approach to achieve kidney regeneration is necessary. The technology of the combination of decellularized kidney scaffolds with stem cells has emerged as a new strategy; however, in previous studies, the differentiation of stem cells in decellularized scaffolds was insufficient for functional kidney regeneration, and many problems remain. METHODS: We used 0.5% sodium dodecyl sulfate (SDS) to produce rat kidney decellularized scaffolds, and induce adipose-derived stem cells (ADSCs) into intermediate mesoderm by adding Wnt agonist CHIR99021 and FGF9 in vitro. The characteristics of decellularized scaffolds and intermediate mesoderm induced from adipose–derived stem cells were identified. The scaffolds were recellularized with ADSCs and intermediate mesoderm cells through the renal artery and ureter. After cocultured for 10 days, cells adhesion and differentiation was evaluated. RESULTS: Intermediate mesoderm cells were successfully induced from ADSCs and identified by immunofluorescence and Western blotting assays (OSR1 + , PAX2 +). Immunofluorescence showed that intermediate mesoderm cells differentiated into tubular-like (E-CAD + , GATA3 +) and podocyte-like (WT1 +) cells with higher differentiation efficiency than ADSCs in the decellularized scaffolds. Comparatively, this phenomenon was not observed in induced intermediate mesoderm cells cultured in vitro. CONCLUSION: In this study, we demonstrated that intermediate mesoderm cells could be induced from ADSCs and that they could differentiate well after cocultured with decellularized scaffolds.